Drivers of Satisfaction With Care for Patients With Lupus. Issue 10 (6th November 2019) - Jolly, Meenakshi; Sethi, Bhavika; O'Brien, Courtney; Sequeira, Winston; Block, Joel A.; Toloza, Sergio; Bertoli, Ana; Blazevic, Ivana; Vilá, Luis M.; Moldovan, Ioana; Torralba, Karina D.; Cicognani, Elvira; et al.
Abstract : Objective: Quality of life (QOL) and quality of care (QOC) in systemic lupus erythematosus (SLE) remains poor. Satisfaction with care (SC), a QOC surrogate, correlates with health behaviors and outcomes. This study aimed to determine correlates of SC in SLE. Methods: A total of 1262 patients with SLE were recruited from various countries. Demographics, disease activity (modified Systemic Lupus Erythematosus Disease Activity Index for the Safety of Estrogens in Lupus Erythematosus: National Assessment trial [SELENA‐SLEDAI]), and QOL (LupusPRO version 1.7) were collected. SC was collected using LupusPRO version 1.7. Regression analyses were conducted using demographic, disease (duration, disease activity, damage, and medications), geographic (eg, China vs United States), and QOL factors as independent predictors. Results: The mean (SD) age was 41.7 (13.5) years; 93% of patients were women. On the univariate analysis, age, ethnicity, current steroid use, disease activity, and QOL (social support, coping) were associated with SC. On the multivariate analysis, Asian participants had worse SC, whereas African American and Hispanic patients had better SC. Greater disease activity, better coping, and social support remained independent correlates of better SC. Compared with US patients, patients from China and Canada had worse SC on the univariate analysis. In the multivariate models, Asian ethnicity remained independently associated with worse SC, even after we adjusted for geographic background (China). No associations between African American or Hispanic ethnicity and SC were retained when geographic location (Canada) was added to the multivariate model. Canadian patients had worse SC when compared with US patients. Higher disease activity, better social support, and coping remained associated with better SC. Conclusion: Greater social support, coping, and, paradoxically, SLE disease activity are associated with better SC. Social support and coping are modifiable factors that should be addressed by the provider, especially in the Asian population. Therefore, evaluation of a patient's external and internal resources using a biopsychosocial model is recommended. Higher disease activity correlated with better SC, suggesting that the latter may not be a good surrogate for QOC or health outcomes.